2008
DOI: 10.1021/bc7004472
|View full text |Cite
|
Sign up to set email alerts
|

Fully Acid-Degradable Biocompatible Polyacetal Microparticles for Drug Delivery

Abstract: A library of polyurethanes and polyureas with different hydrophobicities containing the same acid-degradable dimethyl ketal moiety embedded in the polymer main chain have been prepared. All polymers were synthesized using an AA-BB type step-growth polymerization by reaction of bis(p-nitrophenyl carbamate/carbonate) or diisocyanate monomers with an acid-degradable, ketal-containing diamine. These polymers were designed to hydrolyze at different rates in mildly acidic conditions as a function of their hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
171
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(178 citation statements)
references
References 35 publications
7
171
0
Order By: Relevance
“…Whereas simple degradable polyesters such as polylactic acid, polyglycolic acid and their co-polymers are degraded by acid-catalysed hydrolysis, the hydrolysis rates at even lysosomal pH are so slow that they are not very useful for endosomal delivery. For this reason, more acid-sensitive, hydrolytically sensitive links, such as orthoesters 52 and ketals 53 , have been sought. For example, particles crosslinked with ketal moieties have been developed for biomolecular delivery 53 , including vaccination 54 , through the targeting of endosomal release.…”
Section: Materials For Intracellular Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas simple degradable polyesters such as polylactic acid, polyglycolic acid and their co-polymers are degraded by acid-catalysed hydrolysis, the hydrolysis rates at even lysosomal pH are so slow that they are not very useful for endosomal delivery. For this reason, more acid-sensitive, hydrolytically sensitive links, such as orthoesters 52 and ketals 53 , have been sought. For example, particles crosslinked with ketal moieties have been developed for biomolecular delivery 53 , including vaccination 54 , through the targeting of endosomal release.…”
Section: Materials For Intracellular Targetingmentioning
confidence: 99%
“…For this reason, more acid-sensitive, hydrolytically sensitive links, such as orthoesters 52 and ketals 53 , have been sought. For example, particles crosslinked with ketal moieties have been developed for biomolecular delivery 53 , including vaccination 54 , through the targeting of endosomal release. Endosomal release of CpG oligonucleotides has also been shown to be feasible using these materials chemistries 55 .…”
Section: Materials For Intracellular Targetingmentioning
confidence: 99%
“…In particular, pH-responsive micelles have attracted great attention due to existence of mildly acidic pH in the tumor tissues as well as in the endo/lysosomal compartments of cells [26,27]. Over the past decade, different pH-responsive micelles have been developed based on acid-labile bonds such as ortho ester, hydrazone, cis-acotinyl, and acetal for enhanced intracellular drug release [28][29][30][31][32][33][34][35][36]. We recently reported that biodegradable micelles and polymersomes based on poly(ethylene glycol)-b-poly(mono-2,4,6-trimethoxy benzylidene-pentaerythritol carbonate) (PEG-b-PTMBPEC) block copolymers are prone to rapid hydrolysis thereby "actively" releasing drug under endo/lysosomal pH conditions [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 5 shows a library of acetyl containing acid cleavable polymers created by Fréchet and coworkers [65]. These forms of acid cleavable linkage, are also easy to incorporate into living polymerizations [66,67], the preparation method of choice for many gene vectors [68,69].…”
Section: Intracellular Degradation (Acid/reducing Cleavage)mentioning
confidence: 99%